GAMBARAN KARIES GIGI MOLAR PERTAMA PERMANEN PADA ANAK SD NEGERI 03 SIRAH PULAU PADANG TAHUN 2018 - Sri Wahyuni (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Palembang, 2019)
Caries is a disease that affects children, especially aged 6 years. Not only children who can be affected but alsoadolescent, adult, and even elderly. At the age of 6 years the permanent first molars begin to erupt so that theyare more susceptible to caries. This study aims to determine the description of caries in permanent first molar inchildren at SD Negeri 03 Pulau Padang Sirah in 2018. This study used descriptive research methods. The studypopulation was 110 children with a sample of 86 children. The results showed caries incidence in 50 fourthgrade children reached 58.13%, caries incidence based on tooth elements, permanent lower left first molarcaries with the highest caries incidence rate, there were 35 teeth (36.84%), whereas the right first permanentmaxillary molar were the fewest caries, which is only 11 teeth (11,957%). Based on the age the highestincidence of caries was found at 9 years of age reaching 15 children (30%). It is because children like to eatfoods that contain very high sugar and show a lack of awareness and motivation of parents towards children tomaintain dental health.